Research on the Roof Failure Law of Downward Mining of Gently Inclined Coal Seams at Close Range - Tao Yang; Jiarui Sun; Jie Zhang; Shoushi Gao; Yifeng He; Hui Liu; Dong Liu; Jiayue Deng; Yiming Zhang (Applied Sciences, 2025)
With the increasing depth of coal mining operations, the repeated extraction of multiple coal seams has led to serious safety threats to mines, including secondary roof fracturing, interlayer separation-induced water hazards, and intense mine pressure. Due to the limited research available on the roof failure laws of gently inclined coal seam groups, this study focuses on the Yindonggou Coal Mine and employs a comprehensive approach combining theoretical analysis, numerical simulation, and field measurement. Theoretical calculations indicate that after the mining of Seam 1, the caving zone height ranges from 6.69 to 11.09 m, and the height of the water-conducting fracture zone ranges from 29.59 to 40.79 m. After Coal Seam 2 is mined, the caving zone extends 24.05–33.47 m above the roof of Coal Seam 1, and the fracture zone develops for up to 74.10–94.94 m. Following the mining of Seam 4, the caving zone expands to 30.73–40.15 m above the roof of Coal Seam 1, and the fracture zone reaches 92.26–113.10 m. The numerical simulation results show that after mining Seam 1, the caving zone height is 8.4 m, and the fracture zone reaches 36 m. After Seam 2 is mined, the caving zone extends to 27 m above the roof of Coal Seam 1 and the fracture zone extends to 89 m. After Seam 4 is mined, the caving zone expands to 40 m above the roof of Coal Seam 1 and the fracture zone develops to 112.6 m. The field measurements validate the following findings: a loss of flushing fluid during drilling indicates that after Coal Seam 4 is mined, the fracture zone develops up to 110.5 m above the roof of Coal Seam 1, and the caving zone reaches 47.5 m. Optical imaging logging shows the fracture zone developing to 114.5 m and the caving zone extending to 48.1 m above the roof of Coal Seam 1. The results demonstrate good consistency among these theoretical calculations, numerical simulations, and field measurements. This study reveals a progressive development pattern of roof failure during the repeated mining of gently inclined coal seam groups, providing a theoretical foundation for water hazard prevention and mine pressure control in deep multi-seam mining operations.